The coefficient of consolidation of cohesive oil by using constant rate strain method [electronic resource] - 244142 Abdalla Ali Agwila (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2007